Syntheses, Characterisation, Thermal Analysis and Theoretical Studies of Some Imino Ethanone Metal Complexes - Safaa H. Ali; Saad S. Mohammed; Hadi T. Obaid; Sanjeewa Gamagedara (مجلة بغداد للعلوم, 2024)
The current study is designed to synthesize four new bidentate metal complexes [MCl2L1] M = Co, Cu and L1 = 1,2-Diphenyl-2-(phenylimino)-1-ethanone or  [MCl2L2] M = Co, Cu and L2 = 1,2-Diphenyl-2-(p-tolylimino)-1-ethanone. In addition, theoretical study preforms to predict the chemical reactivity and stability of the prepared complexes. Thus, the density function theory (DFT) studies, quantum chemical descriptors like chemical hardness (η), electronic chemical potential (μ), and electronegativity (χ) are considered. Complexes were synthesized in a simple one-pot reaction and chemical structures confirmed by different analysis techniques such as Mass spectra, FT-IR, UV-Vis spectroscopies and thermo gravimetric analysis (TGA). The prepared complexes showed high level of thermal stability according to analysis results as the melting point of the complexes ranged (249-251 oC).